Geographic Imbalances in Doctor Supply and Policy Responses - Ono, Tomoko (OECD Health Working Papers, 2014)
Doctors are distributed unequally across different regions in virtually all OECD countries, and this causes concern about how to continue to ensure access to health services everywhere. In particular access to services in rural regions is the focus of attention of policymakers, although in some countries, poor urban and sub-urban regions pose a challenge as well. Despite numerous efforts this mal-distribution of physician supply persists. This working paper first examines the drivers of the location choice of physicians, and second, it examines policy responses in a number of OECD countries...